Transvenous extraction of cardiac implantable electronic device leads: the assessment of safety and efficacy - Demurchev, M.F.; Grishin, I.R.; Sapelnikov, O.V.; Ayvazyan, S.A.; Sorokin, I.N.; Kosonogov, K.A.; Cherkashin, D.I.; Ardus, D.F.; Podyanov, M.A.; Kulikov, A.A.; Vereshchagina, A.V.; Emelyanov, A.V.; et al. (Patologii͡a︡ krovoobrashchenii͡a︡ i kardiokhirurgii͡a, 2025)
Introduction: Progressive increase in the number of cardiac implanted electronic devices entails an increment of complications, which require the complete removal of the device system in selected cases. Instruments, such as laser sheath and mechanical dilator introduced into the surgical arsenal, significantly improved the removal of devices and increased the success rate of the procedure. Transvenous lead extraction using additional instruments enables the safe extraction of electrodes in most cases, but does not eliminate the risk of complications, the most significant of which is vascular bed perforation. The hybrid approach, combining transvenous lead extraction with thoracoscopic assistance, allows for visual monitoring of each step of the operation to detect intraoperative complications promptly. Objective: The study aimed to investigate the safety and efficacy of different transvenous lead extraction methods. Methods: One-hundred fifty-four patients, who underwent transvenous extraction of cardiac implantable electronic devices in Chazov National Medical Research Center for Cardiology from 2018 to 2024, were included in the study. Transvenous extraction of leads was performed both on infectious and non-infectious indications. Results: Of the 154 surgical procedures performed, 80 (51.9%) were on infectious indications (group 1) and 74 (48.1%) were on non-infectious indications (group 2). The median age of the electrode was 64 months, (from 30 to 144 months). Between one and five electrodes were removed during each surgical procedure, with an average of two electrodes removed per procedure. Simultaneous reimplantation of a new device was performed in 58 (78.3%) of the 74 patients in the group 2.In 68 cases (44%), the method of simple traction on a locking stylet was chosen as a transvenous electrode extraction technique, while additional instrumentation was used in 86 cases (56%). In particular, a mechanical dilator was used in 14 cases (17%), an excimer laser was engaged in 26 cases (30%), and 2 instruments together were used in 25 cases (29%). The number of hybrid interventions with thoracoscopic control amounted to 21 (24%). Complete extraction of the system was achieved in 128 cases (83.2%), and 26 (17.8%) cases were partially successful (residual electrode fragment value >4 cm). Conversion to open surgery was required in 3 (1.9%) of 154 interventions. Conclusion: Transvenous lead extraction using high-tech tools provides an opportunity to improve the success of the operation. Thoracoscopic control opens up the possibilities of intraoperative visualization of anatomical structures to prevent fatal complications. Received 22 August 2024. Revised 1 December 2024. Accepted 15 January 2025. FundingThe study did not have sponsorship. Conflict of interestThe authors declare no conflict of interest. Contribution of the authorsConception and study design: A.A. Shiryaev, R.S. Akchurin, O.V. Sapelnikov, I.R. GrishinData collection and analysis: M.F. Demurchev, D.F. Ardus, M.A. Podyanov, I.R. Grishin, D.I. Cherkashin, K.A. Kosonogov, S.A. Ayvazyan, I.N. SorokinStatistical analysis: M.F. Demurchev, A.V. Vereshchagina, A.V. EmelyanovDrafting the article: M.F. Demurchev, I.R. Grishin, O.V. Sapelnikov, D.F. ArdusCritical revision of the article: K.A. Kosonogov, S.A. Ayvazyan, I.N. SorokinFinal approval of the version to be published: M.F. Demurchev, I.R. Grishin, O.V. Sapelnikov, S.A. Ayvazyan, I.N. Sorokin, K.A. Kosonogov, D.I. Cherkashin, D.F. Ardus, M.A. Podyanov, A.A. Kulikov, A.V. Vereshchagina, A.V. Emelyanov, A.A. Shiryaev, R.S. Akchurin